A polyvinyl alcohol‐based mixed matrix membrane with uniformly distributed Schiff base network‐1 for ethanol dehydration. Issue 42 (18th April 2020) - Wang, Zhanbin; Liu, Jiahao; Shan, Houchao; Li, Guozhen; Wang, Ze; Si, Zhihao; Cai, Di; Qin, Peiyong
Abstract: In this study, Schiff base network (SNW)‐1 nanoparticles with high hydrophilicity and large specific surface area were used to prepare polyvinyl alcohol (PVA)‐based mixed matrix membranes (MMMs), which were evaluated for ethanol dehydration. Because of the low difference of density between SNW‐1 and PVA, the as‐prepared nanoparticles can be uniformly distributed into the PVA active layer. The effects of SNW‐1 loading, feed temperature, and water concentration on pervaporation (PV) performance were further studied. The results showed the MMM with 10 wt% of SNW‐1 loading exhibited a separation factor of 1, 501 and a permeation flux of 187 g m −2 h −1 for feeding 95 wt% ethanol/water binary solution at 75°C. Overall, the SNW‐1/PVA MMMs showed great prospect in ethanol dehydration via PV. Abstract :